Grammar Problems Faced by Students in Using Simple Present Tense task - Prihatini, Candraning; Kamiliya, Zainina; Pratiwi, Dyah Sih (Journal of English Education, Literature and Linguistics, 2024)
This research is aim to the grammar problems faced by students in learning simple present tense. The participants of this research were students in Universitas Muhammadiyah Lampung who take intermediate grammar class. The samples consisted of seven participants. They are students who take intermediate grammar class. The data collecting technique of this research used observation and students' task to gather data and employed a descriptive design with qualitative analysis to understand and describe the phenomena being studied. This approach is particularly useful for exploring complex behaviors, attitudes, or experiences in depth. Based on the analysis of questionnaire and students’ assignment indicated that this research found that grammar problems faced by students in learning simple present tense were the use; Third-person singular verbs (-s/-es endings) (33 %), Subject-verb agreement (10%), Negative and question forms (5%), Spelling changes with third-person singular (15%), Use of adverbs of frequency (7%), Incorrect use of time expressions (12%), Confusion with stative verbs (8%). Keywords: Grammar Problems, Simple Present Tense, students’ task